Molecular detection and characterization of Anaplasmataceae agents, Bartonella spp. and hemoplasmas in armadillos and anteaters from Brazil - Sada, Jovêncio Mateus [UNESP]; Kluyber, Danilo; Lee, Daniel Antônio Braga [UNESP]; Calchi, Ana Cláudia [UNESP]; Alves, Mario Henrique; Machado, Dália Monique Ribeiro; Werther, Karin [UNESP]; Machado, Rosangela Zacarias [UNESP]; Desbiez, Arnaud Leonard Jean; André, Marcos Rogério [UNESP] (Elsevier, 2024)
Armadillos and anteaters exhibit a wide range of interactions with various pathogens and ectoparasites, which, along with their physiological and ecological characteristics, contribute to their potential as hosts for a broad variety of pathogens with zoonotic potential. However, there has been limited research into the occurrence and diversity of vector-borne agents in this group of mammals. The present study aimed to investigate the occurrence and molecular identity of Ehrlichia spp., Anaplasma spp., Bartonella spp. and hemotropic mycoplasmas (hemoplasmas) in free-ranging armadillos and anteaters sampled in the southeast and central-west regions of Brazil. To this purpose, 167 biological samples (139 blood and 28 spleen) from Xenarthra mammals sampled in the states of São Paulo and Mato Grosso do Sul were analyzed: 48 from six-banded armadillos (Euphractus sexcinctus), 29 from giant armadillos (Priodontes maximus), 4 from nine-banded armadillos (Dasypus novemcinctus), 1 from naked-tailed armadillo (Cabassous unicinctus), 79 from giant anteaters (Myrmecophaga tridactyla) and 6 from southern tamanduas (Tamandua tetradactyla). Screening PCR assays were performed for Ehrlichia spp. based on the dsb gene, nested PCR for Anaplasma spp. and PCR for hemotropic mycoplasmas based on the 16S rRNA gene, and qPCR for Bartonella spp. based on the 16-23S rRNA intergenic region (ITS). The positive samples were additionally subjected to PCR assays targeting different molecular markers for molecular characterization. As a result, 1/48 (0.59%) blood sample from E. sexcintus was positive for Anaplasma spp., and 1/79 (0.59%) blood sample from M. tridactyla was positive for Ehrlichia spp. The 16S rRNA sequence of Anaplasma sp. detected in E. sexcintus clustered within the same clade as 'Candidatus Anaplasma brasiliensis', previously detected in T. tetradactyla. The dsb sequence of Ehrlichia sp. detected in M. tridactyla clustered within the same clade as Ehrlichia minasensis. In the PCR tests for hemoplasmas, 31/46 (64.5%) E. sexcinctus, 9/29 (65.5%) P. maximus, 2/4 (50%) D. novemcinctus, 33/79 (41.7%) M. tridactyla, and 2/6 (33.3%) T. tetradactyla tested positive. The 16S rRNA and 23S rRNA sequences of hemoplasmas found in E. sexcinctus clustered within the same clade as 'Candidatus Mycoplasma haematomaximus', which was previously detected in P. maximus in Brazil. High positivity rates were also observed for Bartonella spp., with 23/48 (47.9%) E. sexcinctus, 1/4 (25%) D. novemcinctus, 9/29 (31%) P. maximus, 21/79 (26.5%) M. tridactyla, and 3/6 (50%) T. tetradactyla showing positive results. The ftsZ sequences of Bartonella sp. detected in E. sexcinctus clustered with 'Candidatus Bartonella washoensis subsp. brasiliensis', previously identified in six-banded armadillos in Brazil. These findings reinforce the presence of 'Candidatus Anaplasma brasiliensis' and 'Candidatus Bartonella washoensis subsp. brasiliensis' in armadillos, and Ehrlichia minasensis in anteaters. This is the first report of ‘Candidatus Mycoplasma haematomaximus’, a hemoplasma previously described in giant armadillos, in six-banded armadillos. The zoonotic potential and real significance of infection by these agents in xenarthrans’ health and conservation efforts are yet to be investigated.
Keywords: Anaplasma spp; Bartonellaceae; Ehrlichia spp.; Hemoplasmas; Molecular diagnosis; Xenarthra